Unit Proses Pembuatan (Grilling - Packing) Terasi untuk Meningkatkan Kapasitas dan Kualitas Produk - Asfan, Asfan (Universitas Trunojoyo Madura, 2008)
Implementation of Ipteks to develop UKM in generating export of non-petroleum supports the increase of national economy in thefuture. This research objective is toincrease · capacity and consumer'staste through technology transfer (grilling-packing). Thefindings showed that the implementation of ipteks was able to increase capacity of products from 150-200 kg per day to 300-400 kg per day or average increase 275 % than traditional ways. It could also increase the quality and taste of terasi and continuity of products being pro 'duced.